Competences for promoting mental health in primary school - Lahti Mari; Korhonen Joonas; Sakellari Evanthia; Notara Venetia; Lagiou Areti; Istomina Natalja; Grubliauskienė Jūratė; Makutienė Monika; Šukytė Daiva; Erjavec Karmen; Petrova Gergana; Lalova Valentina; et al. (SAGE PUBLICATIONS LTD, 2025)
Background:
The mental health od school-age children is of growing concern in many countries. School professionals require the competences and methods to intervene effectively to promote mental health in schools. Objective: The objective of this study was to describe school professionals' perceptions of the competences needed and effective methods to promote mental health in primary schools. Design and setting: Qualitative study conducted in five European countries.
Method:
Multidisciplinary focus group interviews were conducted with teachers, school nurses, psychologists and social workers in Greece (n = 2), Lithuania (n = 3), Slovenia (n = 2), Bulgaria (n = 2) and Finland (n = 2). Data were analysed using qualitative content analysis.
Results:
Competences perceived as required for mental health promotion in primary schools were related to (1) knowledge of child development and mental health among primary school age children, (2) skills such as communication and empathy and (3) teachers' self perception as health promoters. Insufficient attention is currently given to the development of these competences in basic teacher education and ongoing professional development. Providing a safe and inclusive school environment for children and families, early intervention and the use of structured models of support were viewed as effective approaches to use. Digital tools, online materials, and online support were seen as having a valuable role to play in children's mental health promotion.
Conclusion:
School professionals require multiple competences to undertake mental health promotion in primary schools. The development of these competences is best supported by basic and ongoing education. Teachers, school nurses, psychologists and social workers see mixed methods as likely to be most effective in promoting mental health in primary schools.